Global Financial Crises : Institutions and Incentives - Kumar, Manmohan (IMF Working Papers; Working Paper, 2000)
Increasing emphasis has been placed on the need for an effective lender of last resort for sovereign states and on procedures for sovereign debt restructuring to help cope with global financial crises. Where private creditors use short-term debt to check sovereign debtor's moral hazard, there is the risk of self-fulfilling crises. In this context, we conclude that the proposal of the Meltzer Commission-for unconditional financial support, but only to states that pre-qualify-could be the source of increased instability. After discussing analogies with private sector arrangements, we compare the operations of the existing Paris Club with proposed Chapter 11 style procedures.